(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
The article evaluates the influence of environmental factors on the human organism in the conditions of Karakalpakstan. Among the ecological factors, various diseases appear in the human body as a result of the transfer of pollutant compounds to food products through air pollution, water resource pollution, and soil pollution. According to scientific sources, the incidence is high in Moynaq district.